Strategic Partnership between India and the United States: Examining Driving and Restraining Forces - O. Leonova; J. Khatri (Vestnik MGIMO-Universiteta)
This article aims to analyze the historical trajectory and current state of relations between India and the United States, spanning from India's independence in 1947 to the present, with a focus on identifying key stages of development, outcomes, and prospects. The establishment of a strategic partnership between the two countries has evolved through various phases, driven by economic, political, and ideological factors. However, certain limitations hinder the further deepening of this partnership, including disagreements on international political issues, India's pursuit of an independent foreign policy and reluctance to assume a subordinate role, inadequate US support on critical matters, and India's continued cooperation with Russia. Conversely, factors stimulating the growth of the strategic partnership encompass India's robust economic growth, its potential role as a counterbalance to China's expanding influence in Asia, shared interests in maintaining peace and stability in the Indo-Pacific region, mutual concerns about regional security, recent progress in nuclear policy agreements, and expanding avenues for cooperation in diverse domains. The article further examines the unique characteristics of India's relationship with the United States, which shape the nature of their existing strategic partnership, such as the shifting focus from the political and strategic realm to economic interactions, India's commitment to maintaining "strategic autonomy" and non-alignment in its deepening cooperation, its ability to differentiate between political partnership and economic collaboration, and the preservation of a multi-vector foreign policy approach. Based on the analysis, the authors assert that while a strategic military and political alliance between the two powers is unlikely in the near future, their relationship will continue to evolve within the framework of a strategic partnership. The findings of this study will provide insights for policymakers in the South and Southeast Asia region to anticipate developments and adjust their policies accordingly.